International Financial Statistics Yearbook, 2018. (International Financial Statistics; International Financial Statistics ;, 2018)
This 2018 yearbook issue of International Financial Statistics (IFS) is a standard source of statistics on all aspects of international and domestic finance. The IMF publishes calculated effective exchange rates data only for countries that have given their approval. The country, euro area, and world tables provide measures of effective exchange rates, compiled by the IMF's Research Department, Statistics Department, and area departments. The real effective exchange rate index in line rec is derived from the nominal effective exchange rate index, adjusted for relative changes in consumer prices. Consumer price indices, often available monthly, are used as a measure of domestic costs and prices for these countries.